Respuesta :
Hey Astute!
Solve: x^2 - 18x = -72
Solution:
x^2 − 18x − (−72) = −72 − (−72) (Subtract -72 from both sides of the equation)
x^2 − 18x + 72 = 0
(x − 6) (x − 12) = 0 (Factor left side)
x − 6 = 0 or x − 12 = 0 (factors have to equal 0)
6 - 6 = 0 or 12 - 12 = 0
Answer:
x = 6 or x = 12
Hope This Helps, Have a Great Day!
Answer:
ans is x=12 or x=6
same as other but a different way to do it
Step-by-step explanation:
x^2-18x=-72
x^2-2*9x=-72
completing square x^2-2*9x+9^2=-72+9^2
(x-9)^2=-72+81=9
taking square root n add a +/- on left
(x-9) = +/-3
x-9 = 3 or x-9 = -3
x=12 or x=6